STRATEGI PENGEMBANGAN KURIKULUM ADAPTIF BERBASIS KOMPETENSI UNGGULAN LINTAS JENJANG UNTUK PROFIL KARIER PESERTA DIDIK - Siti Raihan; Andi Dewi Riang Tati; Sinta Nurul Oktaviana Kasim; Yulianti; Freddi Sarman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The dynamics of educational transformation in the digital and disruptive era demand schools to develop an adaptive curriculum that aligns with students’ developmental needs, local potential, and future career orientation. This study aims to formulate strategic directions for developing an adaptive curriculum based on signature school competencies across educational levels to establish the continuity of students’ career profiles. Using a qualitative descriptive approach with a systematic literature review method, twenty reputable journal articles were analyzed through content and thematic synthesis. The findings reveal that adaptive curriculum development in Indonesia remains fragmented across educational levels and lacks coherent linkage to students’ long-term career goals. Integration of Holland’s RIASEC career theory provides a scientific framework for understanding career tendencies and embedding them into curriculum design from early education. The study synthesizes five key strategies: (1) early identification of students’ potential and career profiles; (2) formulation of schools’ signature competencies as distinctive identities; (3) progressive curriculum design that ensures cross-level continuity; (4) contextual and project-based learning integration; and (5) adaptive evaluation through career portfolios. This conceptual model positions the adaptive curriculum not merely as an instructional tool but as a transformative framework that empowers every school to develop excellence through unique identities while preparing students to be career-conscious, ethical, and resilient in facing the future of work.